Expression of TCF7L2 in Glioma and Its Relationship With Clinicopathological Characteristics and Patient Overall Survival - Jing, Shiyuan; Chen, Lei; Han, Song; Liu, Ning; Han, MingYang; Yang, Yakun; Yan, Changxiang (Frontiers in Neurology, 2021)
Background: The TCF7L2 gene is known as transcription factor 7-like 2 which has been identified as a novel transcription factor epithelial-mesenchymal transition (EMT) in tumor cells at 10q25.3. TCF7L2 may affect cancer progression and plays a central role in cancer proliferation, migration, and invasion. However, its clinical and prognostic value have not been researched in glioma. The purpose of our study was to research TCF7L2 expression and evaluate the clinical value of prognosis. Method: We collected glioma specimens including low-grade glioma (n = 46) and glioblastoma (n = 51) from September 2015 to September 2017. Expression of TCF7L2 in 97 specimens was detected by quantitative real-time PCR (qRT-PCR). The chi-square test was applied to analyze the relationship between TCF7L2 expression and clinicopathological characteristics. The overall survival (OS) was estimated by log-rank tests among strata, and the survival curves were drawn by Kaplan-Meier. Univariate and multivariate analysis were utilized to analyze the relationship between prognosis and clinicopathological characteristics including TCF7L2 expression. Results: Compared with the low-grade glioma group, the expression of TCF7L2 was significantly increased in the glioblastoma group (p = 0.001). TCF7L2 overexpression was associated with higher WHO grade (p = 0.001), isocitrate dehydrogenase (IDH) wild-type (p = 0.001), and lack of O(6)-methylguanine-DNA methyltransferase (MGMT) methylation (p = 0.001). Moreover, Kaplan-Meier analysis proved that overexpressed TCF7L2 was associated with poor OS (p = 0.010). The multivariate analysis suggested that TCF7L2 expression was an independent prognostic factor (p = 0.020). Conclusions: Our research proved that TCF7L2 was overexpressed in glioblastoma, and related with tumor long-term prognosis, which, therefore, could be an independent prognostic factor for glioma patients.